L-type calcium channel structure and function: mechanisms of gating and signaling in skeletal muscle - Wilkens, Christina M., author (Colorado State University. Libraries, 2002)
L-type channels in muscle function both as voltage-gated Ca2+ channels and as voltage sensors for excitation-contraction (EC) coupling. Potentiation of Ca2+ channels results in a net increase in Ca2+ influx, providing a potent means for regulation of Ca2+ dependent cellular processes. A defining property of L-type channels is their potentiation by both dihydropyridine agonists and strong depolarization. In contrast, non L-type channels are potentiated by neither agonist nor depolarization, suggesting that these two processes may be linked. Here we have tested whether the mechanisms of agonist- and depolarization-induced potentiation in the cardiac L-type channel (otic) are linked. We found that the mutant L-type channel GFP-α1C(TQ→YM), bearing the mutations T1066Y and Q1010M, was able to undergo depolarization-induced potentiation but not potentiation by agonist. Conversely, the chimeric channel GFP-CACC was potentiated by agonist but not strong depolarization. These data indicate that the mechanisms of agonist- and depolarization-induced potentiation of α1C are distinct. Since neither GFP-CACC nor GFP-CCAA was potentiated significantly by depolarization, no single repeat of the α1C can be responsible for depolarization-induced potentiation. Interestingly, GFP-CACC displayed a low channel open probability similar to that of α1C, but could not support depolarization-induced potentiation, demonstrating that a relatively low open probability alone is not sufficient for depolarization-induced potentiation to occur. Thus, depolarization-induced potentiation may be a global channel property requiring participation from all four homologous repeats.

The L-type channel in skeletal muscle (α1S) functions primarily as a voltage sensor for EC coupling. The α1S undergoes a conformational change in response to membrane depolarization, which causes the ryanodine receptor (RyR) in the sarcoplasmic reticulum to release intracellular Ca2+ stores, independent of Ca2+ entry through the channel. The II-III loop of α1S is responsible for bi-directional signaling interactions with the skeletal RyR (RyR1): transmitting the orthograde, EC coupling signal to RyR1 and receiving a retrograde, Ca2+ current-enhancing signal from RyR1. Previous reports had argued for the importance of two distinct regions of the skeletal II-III loop (residues R681-L690 and residues L720-Q765, respectively), claiming for each a key function in DHPR-RyR1 communication. To address whether residues 720-765 of the α1S II-III loop are sufficient to enable bi-directional signaling with RyR1, we constructed a chimera (SkLM) having rabbit skeletal (Sk) α1S sequence except for a II-III loop (L) from the α1 subunit of the house fly, Musca domestica (M). The Musca II-III loop (75% dissimilarity to α1S) has no similarity to α1S in the regions R681-L690 and L720-Q765. Whole-cell patch clamp analysis of SkLM expressed in dysgenic myotubes (which lack endogenous α1S subunits) showed that this construct was unable to mediate bi-directional signaling despite normal surface expression levels and correct junctional targeting (colocalization with Ry R1). Introducing rabbit α1S residues L720-L764 into the Musca II-III loop of SkLM completely restored bi-directional signaling, indicating that this 45 residue "critical domain" is likely to be the only sequence of the α1S II-III loop required for bidirectional coupling.
Keywords: anatomy and physiology; animals; biophysics